Preferences for inter-regional redistribution - Balcells, L; Fernandez-Albertos, J; Kuo, A (SAGE Publications, 2015)
What explains individual support for inter-regional redistribution? Few studies examine support for regional redistribution, even though such issues are politically salient in many democracies. We test models that hypothesize that such preferences are affected by regional and individual income, as well as other arguments beyond the traditional political economy framework. We focus on informational assumptions and implications of these models with an experiment embedded in a nationally representative survey in Spain. We randomly inform some citizens of the true relative income of their region to assess the impact of this information on regional redistribution preferences. We find that citizens’ learning about their region’s relative position affects these preferences in a manner consistent with some of the political economy models. We also find some support for out-group concerns as an important factor. The findings have implications for the applicability of economic models to explaining support for regional arrangements.